﹣2a²×(2分之1ab+b²)-5a(a²b-ab²)
1个回答
答
﹣2a²×(½ab+b²)-5a(a²b-ab²)
=-2a²×½ab-2a²×b²-5a³b+5a²b²
=-a³b-5a³b-2a²b²+5a²b²
=-6a³b+3a²b²
相关问题
分解因式-5a³b²+3a²b,(3分之2ab²-2ab)×2分之1ab
试求ab分之一+(a+1)×(b+1)分之一+(a+2)×(b+2)分之一+……++(a+2004)×(b+2004)分
已知a分之1+b分之1=5求-a+3ab-b分之2a-5ab+2b的值
a√b分之a÷√ab×√ab分之1(b>0)=?
ab分之一+(a+1)×(b-1)分之一+(a+2)×(b+2)分之一+……+(a+2014)×(b+2014)的值,有
1-a^2+ab-4分之1×b^2
a-2b分之a×根号a分之a^2b-4ab^2+4b^3(a>2b)
化简 :a²-2ab分之a²-6ab+9b² 除以(a-2b分之5b²-a-2b
1、5a分之b÷(-a分之2) 2、(a-b)²分之a²-b².ab分之(b-a)²÷a分之a+b
a^2-ab分之(a+b)^2除以[-(a-b)^2分之b^2+ab]